How Occupational Health And Safety (OHS) Practices And The Work Environment Affect Employee Performance, With Job Satisfaction Acting As An Intermediary - Hilma Farhani; Ratih Ayu Sekarini; Wiwin; Riyadi (International Journal of Integrative Sciences, 2025)
The purpose of this study was to determine how how much influence Occupational Health and Safety (OHS) and Work Environment have on Employee Performance mediated by Job Satisfaction at the Ministry of Health of the Republic of Indonesia. East Sunter Warehouse XVII. Research that used is a quantitative method with 76 respondents. respondents. Data collection techniques used The data collection techniques used are company observation, interview with one of the company's one of the company's employees, and distributing questionnaire using google form. in Data analysis was carried out using the Partial Least Square (PLS) method using Smart PLS software. PLS version 4 using Smart PLS software. Data Analysis The data analysis used is validity test, reliability test, Structural Model Test, and hypothesis testing. Research Results and Discussion The results showed that Occupational Health and Safety (OHS) and Work Environment on Employee Performance mediated by Job Satisfaction had a significant effect on employees of the East Sunter Warehouse XVII. from the results of data tabulation and diagrams of thefinal results of the questionnaire, the majority of respondents were respondents. From the results of data tabulation and diagrams of the final results of the questionnaire, the majority of respondents agreed with the statement that Occupational Health and Safety (OHS) and Work Environment, on Employee Performance mediated by Job Satisfaction has a positive effect.